Immunohistochemical characteristics of the endometrium in women with recurrent pregnancy loss and chronic endometritis - S.B. Chechuha; P.M. Nevhadovska; O.A. Nochvina (Publishing House TRILIST, 2022)
Objective: to study endometrium state in women with recurrent miscarriage and chronic endometritis by determining of nuclear cyclin E and syndecan-1, followed by a study of the effectiveness of proposed scheme for managing pregnancy in this category of patients. Materials and methods. Endometrium state (in particular its immunohistochemical characteristics) was studied by determining syndecan-1 in endometrial samples during hysteroscopy or pipelle biopsy in 68 women (main group) with recurrent miscarriage, followed by an analysis of the effectiveness of the proposed schemes of pregravid preparation. The women of the main group were divided into: subgroup 1 (40 pregnant women), whose treatment regimen included antibiotic therapy, folates and micronized progesterone at the pregravid stage; subgroup 2 (28 participants), whose treatment regimen included antibacterial drugs, folate at the pregravid stage and micronized progesterone from early gestation. The control group consisted of 30 re-pregnant women without a history of reproductive losses. Results. Features of the endometrium state in women with recurrent miscarriage are characterized by the presence of the CD138 protein (syndecan-1) and an abnormal (elevated) level of nuclear cyclin E, which indicates a morphological reorganization of the endometrial layer and its unpreparedness for successful implantation and further gestation. This study proved successful correction of the endometrium state at the stage of preconception preparation due to the use of micronized progesterone Utrogestan®, which consisted in reducing the percentage of reproductive losses, improving the course of pregnancy and childbirth. Conclusions. Utrogestan is a reliable, safe and effective treatment for women with recurrent miscarriage against the background of chronic endometritis even at the stage of preconception preparation. Such regimen allows transforming the endometrium and preparing it for implantation, thereby significantly improving the microenvironment for the early embryo development and successful pregnancy.